2005
DOI: 10.1175/jas3559.1
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variations of Total Ozone at Northern Midlatitudes Correlated with Stratospheric EP Flux and Potential Vorticity

Abstract: At northern midlatitudes over the 1979-2002 time period, column ozone trends are observed to have maximum negative amplitudes in February and March. Here, the portion of the observed ozone interannual variability and trends during these months that can be attributed to two specific dynamical transport processes is estimated using correlative and regression methods. In approximate agreement with a recent independent study, 18%-25% of the observed maximum negative trend is estimated to be due to long-term change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 78 publications
7
75
0
Order By: Relevance
“…3a), TCO decreases at different rates in different regions, although the TCO over the whole middle latitudes show negative trends, as reported by previous studies (e.g. Callis et al 1997;Hadjinicolaou et al 2005;Hood and Soukharev 2005). The maximum negative TCO trend occurs over East Asia and the TCO decline over northwestern North America is weak, as is more evident in the linear trends of the zonal TCO anomalies (Fig.…”
Section: Zonally Asymmetric Ozone Trend and Its Influencing Factorssupporting
confidence: 82%
See 1 more Smart Citation
“…3a), TCO decreases at different rates in different regions, although the TCO over the whole middle latitudes show negative trends, as reported by previous studies (e.g. Callis et al 1997;Hadjinicolaou et al 2005;Hood and Soukharev 2005). The maximum negative TCO trend occurs over East Asia and the TCO decline over northwestern North America is weak, as is more evident in the linear trends of the zonal TCO anomalies (Fig.…”
Section: Zonally Asymmetric Ozone Trend and Its Influencing Factorssupporting
confidence: 82%
“…However, some studies have shown that stratospheric ozone concentrations over different regions along the same latitude exhibit different recovery rates. Over some regions, TCO even continues to decrease due to changes in local dynamical and chemical processes (Hood and Soukharev 2005;Zhang et al 2014Zhang et al , 2018Wargan et al 2018), suggesting that long-term ozone variations are highly longitude-dependent. Previous studies pointed out that the trends in the deviation of ozone from the zonal mean over some regions can reach and even exceed the zonal mean ozone trend at that latitude, particularly at 1 3 northern middle latitudes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase of total ozone during ENSO-III (1997-1998) was accompanied by decreased precipitation, producing extensive forest fires in Indonesia, Australia, and South America (46,47). The influence of ENSOs on total columnar ozone has been attributed to the variation in the tropopause height driven by changes of tropical deep convection and alteration of Brewer-Dobson circulation (14,48). These observations suggest that the Δ 17 O of sulfate aerosols can be used to track moderate to strong ENSO events and the variation in ozone concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The observed dataset reflects the range of processes contributing to the observed oxygen isotopic composition of sulfate. during ENSO periods (14,48). Cumulatively, all components needed to provide ENSO-related Δ 17 O enrichments are present.…”
Section: Discussionmentioning
confidence: 99%
“…The latter dynamical processes include a) the indirect effect of mixing of chemically ozone-depleted Arctic and Antarctic air to lower latitudes (e.g., Chipperfield 1999), and b) the direct effect of long-term (e.g., climate-related) changes in stratospheric circulation on the ozone column without changes in chemical losses (e.g., Fusco and Salby 1999;Hood and Soukharev 2005). In the chapter summary, it is stated: "While some studies suggest a role for a purely dynamical trend in midlatitude ozone depletion, these have not yet succeeded in quantifying a significant independent contribution."…”
Section: Aeronomy Of the Middle Atmosphere: Chemistry And Physics Of mentioning
confidence: 99%